Role of Risk Assessment and Mitigation in Strategic Planning in Nigeria - Olumide, Samuel (International Journal of Strategic Management, 2023)
Purpose: The aim of the study was to investigate the role of risk assessment and mitigation in strategic planning in Nigeria. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library Findings: The study on risk assessment and mitigation in Nigerian strategic planning reveals a recognition-action gap in organizations. Despite understanding the importance of risk management, many lack a structured approach to address threats. Common risks include political instability, security concerns, corruption, regulatory changes, and economic volatility. To improve decision-making and stakeholder value, the study recommends a more integrated and systematic approach to risk management within Nigerian organizations. Unique Contribution to Theory, Practice and Policy: Game Theory, Resource-Based View (RBV) Theory & Institutional Theory may be used to anchor future studies on the role of risk assessment and mitigation in strategic planning in Nigeria. Nigerian strategic planning should create context-specific risk maps that outline the geographical distribution of risks and vulnerabilities within the country. Nigerian policies should prioritize investments in building resilience to identified risks.